Odpowiedzi

Najlepsza Odpowiedź!
2009-11-28T00:01:59+01:00
20/86

a) n²(n-1)(n²+1) = (n³-n²)(n²+1) = n5 - n4 + n³ - n²
ta 5 i 4 przy 'n' to też potęgi . ;p
b) n²(n+1)(n²-1) = (n³+n²)(n²-1) = n5 + n4 - n³ - n²
c) (a - b)(a² + ab + b²) = a³ + a²b + ab² - a²b - ab² - b³ = a³-b³
d)(x² + x + 1)(x² - x + 1) = x4 - x³ + x² + x³ - x² + x + x² - x + 1 = x4 + x² + 1

7/76

a) a × 3b√2 = 3ab√2
b) x√5 × y√3 = xy√15
c) ⅓a × a²/2√6 = 1/6a³√6

10/77

a) x + (3x - y² +7) = x + 3x - y² +7 = 4x - y² +7
b) -a + (2a - 3b -1) = -a + 2a - 3b - 1 = 3a - 3b - 1